Exercise Improves Myocardial Deformation But Not Cardiac Structure in Preterm-Born Adults - Lapidaire, Winok; Mohamed, Afifah; Williamson, Wilby; Huckstep, Odaro J.; Alsharqi, Maryam; Tan, Cheryl M.J.; Burden, Samuel; Dockerill, Cameron; Woodward, William; McCourt, Annabelle; Burchert, Holger; Kenworthy, Yvonne; et al. (JACC. Advances (Online), 2025)
People born preterm (<37 weeks' gestation) have a potentially adverse cardiac phenotype that progresses with blood pressure elevation. The authors investigated whether preterm-born and term-born adults exhibit similar cardiac structural and functional remodeling following a 16-week aerobic exercise intervention. We conducted a randomized controlled trial in 203 adults (aged 18-35 years) with elevated blood pressure or stage 1 hypertension. Participants were randomized 1:1 to a 16-week aerobic exercise intervention or to a control group. In a prespecified cardiovascular magnetic resonance imaging (CMR) substudy, CMR was performed at 3.0-Tesla to assess left and right ventricular (LV and RV) structure and function before and after intervention. A total of 100 participants completed CMR scans at baseline and after the 16-week intervention, with n = 47 in the exercise intervention group (n = 26 term-born; n = 21 preterm-born) and n = 53 controls (n = 32 term-born; n = 21 preterm-born). In term-born participants, LV mass to end-diastolic volume ratio decreased (−3.43; 95% CI: −6.29 to −0.56; interaction P = 0.027) and RV stroke volume index increased (5.53 mL/m2; 95% CI: 2.60, 8.47; interaction P = 0.076) for those in the exercise intervention group vs controls. No significant effects were observed for cardiac structural indices in preterm-born participants. In preterm-born participants, LV basal- and mid-ventricular circumferential strain increased (−1.33; 95% CI: −2.07 to −0.60; interaction P = 0.057 and −1.54; 95% CI: −2.46 to −0.63; interaction P = 0.046, respectively) and RV global longitudinal strain increased (1.99%; 95% CI: −3.12 to −0.87; interaction P = 0.053) in the exercise intervention group vs controls. No significant effects were observed for myocardial deformation parameters in term-born participants. Aerobic exercise training induces improved myocardial function but not cardiac structure in preterm-born adults. [Display omitted]